Learn PHP 7 Object Oriented Modular Programming using HTML5, CSS3, JavaScript, XML, JSON, and MySQL - Prettyman, Steve (Apress : Imprint: Apress, 2016)
This book is packed with over seventy PHP 7 (and PHP 5.6) functions. Programming examples take advantage of the newest PHP features, including enhanced password encryption using password_hash. This book provides 'learn by doing' providing the reader with complete coding examples. What You'll Learn What are PHP language basics: conditional statements, loops, arrays, methods (functions) How to combine PHP with HTML5, CSS3, and JavaScript to create web applications How to work with XML, JSON, and MySQL data How to use secure coding techniques How to create error logs, user logs, and application logs What are the various backup and recovery techniques How to use Try/Catch blocks as emphasized with PHP 7 to handle program exceptions .